Intention to Saving of Z Generation at Islamic Bank in Bandung Raya - Indah Kumala Sari; Mochamad Edman Syarief; Dwi Suhartanto (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
A phenomenon the low number of customers using Islamic banking compared to conventional banking in Indonesia, where the majority of the population is a Muslim. Then, potential islamic bank customer groups are students or people with an age range between 18 to 24 years, which is the potential of West Java Province as the largest population of Z generation. The research objective to analyze the factors that influence individual behavioral intentions to saving in islamic bank by using the Theory of Planned Behavior (TPB). 100 questionnaires were distributed to people belonging to the Z generation category in Bandung Raya. Data from the questionnaire were analyzed using structural equation modeling (SEM). Results explain there is a positive effect of intention on saving behavior, positive effect of subjective norms on intention, positive effect of PBC on intention, the effect of religiosity on intention, and positive effect of costumer satisfaction on saving behavior.